Land Resources Inventory In Developing Countries : A Problem of Collecting and Generating Relevant Data A Typical Case of Atmospheric Water Balance Inventory. - Tejoyuwono Notohadiprawiro (Jurnal Ilmu Pertanian, 1986)
-